An impact of country-specific economic developments on ECB decisions - Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The discussion about country-specific influence on the interest rate decisions of the European Central Bank does not cease. To investigate the possibility of regional influence on the determination of the policy rate, we estimate Taylor-type reaction functions for the period from 1999 to 2005 and include country-specific variables of the euro zone member states. We do not find convincing evidence that country-specific economic developments influence the decisions of the ECB Governing Council. However, the maximum inflation rate and the minimum economic sentiment of the euro area seem to have an effect on the decisions.
Keywords: E52; E58; 330; Taylor rule; ECB; monetary policy